DIDACTIC OPPORTUNITIES FOR STUDENTS’ PERSONAL AND PROFESSIONAL SELF-DEVELOPMENT (Web of Teachers: Inderscience Research, 2024)
This article examines the didactic possibilities of personal and professional self-development of students and their assimilation of knowledge.